Infusão intra-hipocampal de espermidina melhora a persistência da memória e a persistência da reconsolidação da memória em ratos - Signor, Cristiane (2016)
The persistence of memory requires a delayed healing process (12-24 h after the acquisition) wherein the synthesis of new proteins and derived neurotrophic factor (BDNF), are essential. The polyamines putrescine, spermidine (SPD) and spermine, they act as endogenous modulators of various ion channels, including the glutamatergic receptor subtype N-methyl-D-aspartate (NMDAr). Systemic administration and intracerebral SPD improves memory in various tasks in rodents. It has recently been demonstrated that systemic administration of SPD improves the persistence and reconsolidation of memory in contextual fear conditioning task in rats. However, there are few studies to elucidate the mechanism of action and the brain structures involved in the effect of polyamines in these stages of memory. Therefore, the aim of this study was to evaluate the effect of intra-hippocampal infusion of SPD in the persistence of memory and the persistence of memory reconsolidation of animals subjected to contextual fear conditioning task. Also, check the involvement of NMDAr, protein synthesis and protein kinase dependent on cAMP (PKA), in the persistence of memory. We also investigated the involvement of BDNF expression and neurogenesis in persistent memory reconsolidation. Thus, adult male Wistar rats were submitted to training in contextual fear conditioning task, and 12 h post-training, received an intra-hippocampal infusion SPD (0.02-2 nmol/site), arcaine (0.02-2 nmol/site), a competitive antagonist of the polyamine NMDAr binding site as well as the protein synthesis inhibitor (anisomycin, 2-20 μg/site) and PKA inhibitor (H- 89 0.5-10 pmol/site). One group of animals was euthanized, 3 h after injection of SPD, for further evaluation of the expression of hippocampal PKA. Another group of animals was tested 2 or 7 days after training. While intra-hippocampal infusion SPD (2 nmol/site) improved the persistence of memory, arcaine (2 nmol/site) and anisomycin (20 μg/site) impaired the persistence of memory of the animals tested 7 days after training. The arcaine (0.2 nmol/ site), the anisomycin (2 μg/site) and H-89 (10 pmol/site), at doses that have no effect per se, prevented the improvement of the persistence of memory induced by SPD (2 nmol/ site). The SPD (2 nmol/site) increased the expression of phospho-PKA/total-PKA, while the H-89 (10 pmol/site) prevented the increase in phospho-PKA/total-PKA-induced SPD. In addition, we evaluated the effect of polyamines in persistent memory reconsolidation. For this, Wistar adult male rats were trained in contextual fear conditioning task, 24 h post- training memory has been reactivated, and 0, 6, 12 or 24 h post-reactivation received an intra-hippocampal infusion SPD (0.02- 2 nmol/ site). One group of animals was euthanized 3 h after injection of SPD and the hippocampus was removed for later evaluation of the expression of total and mature BDNF. Another group of animals was tested 2 or 7 days after the reactivation. The SPD (2 nmol/site) infused 0 h and 12 h post-reactivation, improved the persistence of reconsolidation of memory, only in animals tested 7 days after reactivation. Moreover, the SPD (2 nmol/site) infused 12 h after reactivation increased the expression of mature BDNF, but not the total BDNF in rat hippocampus. In vitro studies demonstrated that the SPD increased the number of neurites, migration cell and levels of BDNF in neural progenitor cells. Therefore, the present results suggest an upregulation of polyamines in hippocampal NMDAr, protein synthesis and PKA in the memory persistence phase. This study also suggests the involvement of the SPD in persistent memory reconsolidation probably through mechanism to facilitate the increase in mature hippocampal BDNF expression and neurogenesis.